(untitled) (Journal of Social Sciences Review, 2023)
The aim of such a research paper is to identify the impacts of coach behavior on the motivation of student-athletes at the university level. A quantitative method of research is used with a descriptive research design and also follows the cross-sectional method of survey. A total of 370 student-athletes were included as samples from different public sector universities of Khyber Pakhtunkhwa (KP) Pakistan. The researcher has used two different scales, i.e. Coach Behavior and Athlete’s Motivation, for the collection of data from the respondents. The output of the study corresponds with the literature. It was concluded that coach behavior has a substantial impact on the motivation of student-athletes at public sector universities in KP Pakistan. Keeping in mind the restriction of the study, more investigations are needed to modify the findings. The current study has made efforts to provide realistic data to the public sector universities of KP, which will support the coaches to apprehend the coaching techniques to increase the motivation of the student-athletes at the university level.